PENGEMBANGAN E-MODUL BIODIVERSITAS MANGROVE TAMAN NASIONAL BUNAKEN DENGAN STRATEGI PEMBELAJARAN PROJECT BASED LEARNING MAPALUS - Pasaribu, Vera Laspita; Wurarah, Masje; Posumah, Dany Ch (SOSCIED, 2025)
The development of media as a learning resource in learning has a very close correlation with technology. E-modules are suitable media for use in project based learning strategy learning. This study aims to develop learning media in the form of e-modules with mangrove biodiversity material with a practical mapalus strategy to use. The development model used in this study is ADDIE with 5 stages, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The results of the media expert validation obtained 91% with a very feasible category, the validation of material experts obtained 85,3% with a very feasible category, the assessment of biology teachers obtained 90% with a very feasible category and the results of the questionnaire obtained from students 91% with a very feasible category which means that the media developed is feasible to use as a medium in learning.